Cellular Mechanisms Underlying Eosinophilic and Neutrophilic Airway Inflammation in Asthma - Girolamo Pelaia; Alessandro Vatrella; Maria Teresa Busceti; Luca Gallelli; Cecilia Calabrese; Rosa Terracciano; Rosario Maselli (Mediators of Inflammation)
Asthma is a phenotypically heterogeneous chronic disease of the airways, characterized by either predominant eosinophilic or neutrophilic, or even mixed eosinophilic/neutrophilic inflammatory patterns. Eosinophilic inflammation can be associated with the whole spectrum of asthma severity, ranging from mild-to-moderate to severe uncontrolled disease, whereas neutrophilic inflammation occurs mostly in more severe asthma. Eosinophilic asthma includes either allergic or nonallergic phenotypes underlying immune responses mediated by T helper (Th)2 cell-derived cytokines, whilst neutrophilic asthma is mostly dependent on Th17 cell-induced mechanisms. These immune-inflammatory profiles develop as a consequence of a functional impairment of T regulatory (Treg) lymphocytes, which promotes the activation of dendritic cells directing the differentiation of distinct Th cell subsets. The recent advances in the knowledge of the cellular and molecular mechanisms underlying asthmatic inflammation are contributing to the identification of novel therapeutic targets, potentially suitable for the implementation of future improvements in antiasthma pharmacologic treatments.